Boy–Girl Differences in Pictorial Verbal Learning in Students Aged 8–12 Years and the Influence of Parental Education - van Tetering, Marleen A. J.; de Groot, Renate H. M.; Jolles, Jelle (Frontiers in Psychology, 2018)
This large-scale cross-sectional study of schoolchildren aged 8–12 years (N = 152) evaluates two factors which potentially determine individual differences in intentional learning: the child’s sex and parental education. Intentional learning was assessed with a newly constructed Pictorial Verbal Learning Task (PVLT). This task presents line drawings of concrete objects as to-be-remembered information instead of written or auditory presented words. The PVLT has the advantage that performance is not confounded by individual differences in reading abilities or by hearing difficulties. Results revealed clear sex differences in performance: Girls outperformed boys. Parental education also contributed to individual differences in performance since children of higher educated parents outperformed children of lower educated parents. The results therefore suggest that both sex and parental education could be potent contributors to individual differences in learning performance at school. The findings more specifically imply that children of less educated parents and boys need additional guidance and support in intentional learning when new information and procedures are presented for the first time.